Relasi Konseptual antara Komunikasi Organisasi dan Budaya Organisasi: Suatu Kajian Teoretis - Atjih Sukaesih; Yantos Yantos (Al-Manar Journal of Economic and Social Studies, 2025)
Organizational culture is a system of values, beliefs, assumptions, or a norm that has been applied, agreed upon and followed by human resources in an organization as a principle or guideline and solving problems that arise in an organization. In building an organizational culture, of course, each organization, regardless of the type and level of the organization, has different experiences in some circumstances and has a similarity in certain circumstances. This indicates that there is dynamism in an organization in building organizational culture as a guideline and principle for each individual in an organization in carrying out their respective duties and obligations to succeed in building organizational goals. Organizational culture is born from a long process starting from the beginning of the establishment of the organization to the formation phase and to the success phase. A long journey, both in the form of failure and success is a journey that is then used as a foothold in building organizational culture.